2021
DOI: 10.1029/2020pa004053
|View full text |Cite
|
Sign up to set email alerts
|

Bentho‐Pelagic Decoupling: The Marine Biological Carbon Pump During Eocene Hyperthermals

Abstract: The marine biological carbon pump sequesters carbon from the atmosphere into deep ocean waters and to a lesser extent, in seafloor sediments (Figure 1). Despite focused study, many questions remain regarding carbon cycle functioning and potential changes in a warming world-changes that will affect oceanic ecosystems and potentially serve as feedbacks to the climate-carbon cycle system (e.g., IPCC, 2014; Passow & Carlson, 2012). Today, the ocean sequesters a third to a quarter of anthropogenic carbon dioxide em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 103 publications
(239 reference statements)
0
12
0
Order By: Relevance
“…However, we know that temperatures were predominantly warm and stable throughout the Danian, with the only departure being the few degrees C of warming associated with the Dan-C2 event. Griffith et al (2021) examined changes in benthic foraminifera and barium flux across Eocene hyperthermals and found that warming caused increased remineralization of organic matter below the euphotic zone, recorded as an increase in Ba and a decline in benthic foraminifera. Unfortunately, the characteristic carbon isotope excursion associated with the Dan-C2 hyperthermal cannot be identified in our core, likely due to both the aforementioned diagenetic alteration and slow sedimentation rates.…”
Section: Testing the Two Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we know that temperatures were predominantly warm and stable throughout the Danian, with the only departure being the few degrees C of warming associated with the Dan-C2 event. Griffith et al (2021) examined changes in benthic foraminifera and barium flux across Eocene hyperthermals and found that warming caused increased remineralization of organic matter below the euphotic zone, recorded as an increase in Ba and a decline in benthic foraminifera. Unfortunately, the characteristic carbon isotope excursion associated with the Dan-C2 hyperthermal cannot be identified in our core, likely due to both the aforementioned diagenetic alteration and slow sedimentation rates.…”
Section: Testing the Two Hypothesesmentioning
confidence: 99%
“…Another possibility that must be addressed is the effect of temperature on metabolic rates of grazers, with warmer waters facilitating increased remineralization of sinking organic matter, essentially making the biological pump less efficient (e.g., Boscolo-Galazzo et al, 2021;Griffith et al, 2021). Unfortunately, pervasive diagenetic alteration of carbonates means that it is not possible to make meaningful interpretations of temperature trends at Site M0077 using the bulk carbonate oxygen isotope record.…”
Section: Testing the Two Hypothesesmentioning
confidence: 99%
“…[2021]). The amount of NPP that reaches the deep sea varies by region and is largely controlled by plankton ecology (Henson et al., 2012), but on the whole only 1%–3% of modern NPP reaches the deep ocean or sediments (e.g., de la Rocha and Passow, 2007; Griffith et al., 2021; Müller & Suess, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…POM which sinks below the mesopelagic zone is effectively removed from the short-term carbon cycle, and so the export of organic matter below 1000 m is often referred to as "sequestration flux" (e.g., Passow and Carlson, 2012) or "transfer efficiency" (Henson et al, 2012). By this point, most remineralization has occurred, but POM sinking out of the mesopelagic zone has traveled through less than one third of the average depth of the ocean, and additional remineralization occurs all the way to (and at) the seafloor, before surviving POM is buried and removed from the carbon cycle on geologic time scales (referred to as "burial flux" by Griffith et al, 2021). The amount of net primary production that reaches the deep sea varies by region and is largely controlled by plankton ecology (Henson et al, 2012), but on the whole only 1-3% of modern net primary production reaches the deep ocean or sediments (e.g., Müller and Suess, 1979;de la Rocha and Passow, 2007;Griffith et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation